Análisis de la sostenibilidad económica ambiental de una unidad de producción agroforestal, ubicada en el eje de Carretera Iquitos – Nauta, km 67,66, Loreto, Perú, 2022 - Tapullima Cenepo, Lissy Geannella Morellia (2024)
The present study has been developed in the production units of the Iquitos-Nauta Road axis, 67,66 km, owned by Julio Ahuanari Robalino, Pedro Zumaeta Valera; with the purpose of determining the progress of the environmental economic sustainability of the production unit owned by Mr. Julio Robalino Ahuanari and Pedro Zumaeta Valera. From the obtained results, production unit N°66, owned by Mr. Julio Robalino Ahuanari, does not meet the objective of socio-economic environmental because the forest is too thinned which prevents the development of high-quality agricultural species and similarly the forest aspect that does not meet the minimum conditions for a forest recovery process. Production unit N°67, owned by Mr. Pedro Zumaeta Valera, also does not meet the objective of social economic environmental sustainability because the forest is too deteriorated by legal and illegal extraction, which prevents its rapid recovery and is also not possible with only a very limited agricultural area. The two exploitation units are in similar conditions, so greater attention is necessary on the part of the authority of the sector. The income of the owners of the production processes is located at levels D and E.